REGENERASI KEPEMIMPINAN DAN DINAMIKA ORGANISASI DI PONDOK PESANTREN TRADISIONAL DAN MODERN - Muhammad Rizman Reza; Abunazar Alim; Khairul Anam; Shofwan Manaf (Merwin Publisher, 2026)
Leadership regeneration is a determining factor for the sustainability of boarding school organizations, both traditional and modern. Boarding schools as value-based Islamic educational institutions face increasingly complex organizational dynamic challenges, especially related to the transition of leadership from one generation to the next. This article aims to analyze leadership regeneration and organizational dynamics in traditional and modern Islamic boarding schools through a conceptual approach based on literature review. This research uses a systematic literature review method sourced from accredited national journals and reputable international journals that are open access, as well as relevant academic books. The results of the study show that traditional boarding schools tend to rely on regeneration patterns based on charisma and lineage, while modern boarding schools are starting to develop structured and managerial regeneration systems. The conceptual contribution of this article lies in the comparative synthesis of leadership regeneration patterns in traditional and modern Islamic boarding schools and their implications for the dynamics of Islamic boarding school organizations in Indonesia.